Rancang Bangun Visualisasi Informasi Sales Achievement TV Berlangganan Menggunakan Sistem Dashboard Di Telkomvision Regional Office Bali Nusra - I Putu Mulya Gunawan; Anjik Sukmaaji; Erwin Sutomo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2014)
Abstract: Telkomvision is a subsidiary of Telkom Indonesia which engaged business on pre-paid TV subscription and has some branch office called RO. At this time the size of sales performance measurement is shown by using table which is difficult to read and couldn’t see more detail number of subscriber achievement to general manager so that when it is forwarded to the subordinates there could have been errors. Problems on Telkomvision RO Bali Nusra can be handled by visualization information sales achievement of pay TV using dashboard system. Dashboard can give an easy look to general manager nor sales manager regarding company condition so that can help them to make a decision. Based on application trial using customer data, sales achievement information could be shown more simple and suitable with key performance indicator. The result shows that information visualization which made can help Telkomvision RO Bali Nusra on performance monitoring and making decision to achieve sales target.